PREDIKSI KEBUTUHAN AIR PDAM GIRI TIRTA SARI KABUPATEN WONOGIRI MENGGUNAKAN METODE SEASONAL AUTOREGRESSIVE INTEGRATED MOVING AVERAGE (SARIMA) - PUSPITA, DEVIANA; FITRIYADI, FARID; KHUSNULIAWATI, HARDIKA (STMIK KAPUTAMA, 2025)
This study aims to predict the clean water needs of PDAM Giri Tirta Sari in Wonogiri Regency using the Seasonal Autoregressive Integrated Moving Average (SARIMA) method. Clean water is a vital necessity for the community, and fluctuations in water demand pose a challenge for PDAM in managing water availability. This study utilized historical data on water usage per month from January 2020 to December 2024, sourced from PDAM operational records. The SARIMA method was chosen because of its avility to handle seasonal time series data. The result show that the best model produced a MAPE value of 8,37%, MAE 50,73 , and RMSE 57,06 . Based on the prediction evaluation standards, an MAPE value <10% is included in the category of high prediction accuracy. The resulting that the demand for clean water uncreases during the dry season. This study is expected to be the basic for planning in water resource management by PDAM.